Phytohormones enhance resistance to Tenebrio molitor by regulating reactive oxygen species and phenolic metabolism in pigeon pea - Yang, Jie; Li, Hongquan; Zhang, Su; Zhang, Yuexin; Xie, Jianbo; Wink, Michael; Fu, Yujie (Physiologia plantarum, 2025)
Pigeon pea is an important economic crop with medicinal and nutritional value. Unfortunately, pest infestation of leaves during postharvest storage seriously affects the quality of pigeon pea. Phytohormones play a crucial role in disease and pest defence by regulating the accumulation of specialized metabolites. Still, their impact on the postharvest storage of pigeon pea has not been reported. In this study, the physiological parameters and main phenotypes of pigeon pea leaves treated with MeJA, ABA, and GA were investigated for the first time. The activity of the antioxidant enzyme system, which eliminates reactive oxygen species, was enhanced by applying MeJA, GA, and ABA. MeJA, GA, and ABA significantly affected crown width, plant height, and relative water content in pigeon pea, respectively. Metabolomic profiling analysis identified phenolic compounds as the main differentially accumulated metabolites (DAMs). UPLC-QqQ-MS/MS identified stilbenes, flavanones, flavones, isoflavones and anthocyanins as major phenolic compounds responsive to MeJA, GA, and ABA induction. By feeding insects, it was found that the insects fed on MeJA-, ABA-, and GA-treated leaves less than on control leaves. Correlation analysis confirmed that isoflavones play an important role in this process. Moreover, the expression of key genes involved in flavonoid biosynthetic pathways and anti-insect-related genes was regulated by MeJA, GA, and ABA. Overall, this work provides a new strategy for the cultivation and storage of pigeon pea or other commercial crops and preliminarily clarifies that flavonoid metabolites under plant hormone treatment can promote plant growth and defence against insects by regulating reactive oxygen species.